Gastrocnemius muscle structure and function in habitually resistance-trained marathon runners and traditionally running-trained marathon runners: a comparative analysis - Ellis, Tracy (Division of Physiotherapy, 2017)
Background: Marathon running involves running long distances and is associated with a high prevalence of running-related injuries. The calf has been identified as one of the most commonly injured structures during running. Running training causes an overload on muscle and stimulates a physiological adaptation to create a training response. Specific adaptations in metabolic and physiological function of a muscle may be further achieved through specificity of exercise training. Resistance training programmes are commonly implemented to enhance specific muscle strength and endurance; and are effective methods of performance and injury prevention. While evidence-based guidelines for resistance training exist, it is unclear whether runners are routinely incorporating evidence-based resistance training into marathon training programmes. If runners are performing habitual resistance training, it is also unknown if the resistance training is of sufficient magnitude or intensity to induce dose-related responses in calf muscle structure or function. Aim: The aim of this study was to evaluate gastrocnemius muscle structure and function in marathon runners who performed habitual resistance training in addition to regular endurance training, compared to marathon runners who performed traditional endurance running training only. Specific Objectives: • To describe the demographic and training characteristics of habitually resistance-trained marathon runners and traditionally running-trained marathon runners. • To determine if there were differences in gastrocnemius endurance, power and flexibility between habitually resistance-trained marathon runners and traditionally running-trained marathon runners. • To evaluate if there were differences in the gastrocnemius muscle structure and architecture in habitually resistance-trained marathon runners compared to traditionally running-trained marathon runners. • To establish if there were any differences in the number of calf injuries sustained in habitually resistance-trained marathon runners and traditionally running-trained marathon runners. Methods: Healthy male runners between 20 and 50 years were included in the study. Participants were required to have completed at least one marathon in the 12-month period prior to the study. Runners forming the "traditionally running-trained" group were required to be participating in regular endurance running training only. Runners in the "habitually resistance-trained group" were required to be performing resistance training in addition to regular endurance running training. Runners with any injury at the time of recruitment or runners who reported a calf injury within the six-month period prior to the study were excluded. Participants with any medical abnormalities detected during screening were also excluded from the study. Eight marathon runners participating in habitual resistance training plus standard running training and eleven marathon runners participating in traditional running training only were recruited for this study. Runners who met the criteria attended two testing sessions at least three days apart. During the first session, informed consent was obtained and the Physical Activity Readiness Questionnaire (PAR-Q) was completed to ensure participants could safely complete physical testing. A questionnaire was completed to determine relevant training and injury history. Body mass, height and the sum of seven skinfolds were recorded. Muscle architecture measurements, including fascicle length, pennation angle, thickness and volume, were performed via imaging ultrasound. Participants were then familiarised with the physical testing procedures. In the second testing session, calf muscle flexibility and endurance were assessed; and isokinetic testing was performed for the left and right triceps surae. Results: There were no significant differences in descriptive characteristics between groups. Participants in the habitually resistance-trained group performed in an average of two hours (range 0.5-2.5 hours) of resistance training of between one to four sessions per week. Participants combined upper and lower body training in the form of circuit training, body weight training, core and proprioceptive training. Resistance training sessions were performed at a varied intensity for load (light to high) according to an estimated 1RM. Participants in the habitually resistancetrained group had completed a significantly greater number of 21.1 km races compared to the traditionally running-trained group (p < 0.05); but there were no other differences in running training or competition history between groups. There were also no significant differences in the number of reported injuries between groups. Average pennation angle was significantly increased in the habitually resistance-trained group compared to the traditional running-trained group (p < 0.05). No other significant differences in architectural measurements were identified. There were no significant differences in calf muscle flexibility, strength, power or endurance between the two groups. However, the small sample size limits the interpretation of the study findings. Conclusion: Wide variability in habitual resistance training patterns were identified. While pennation angle was significantly greater in the habitually resistance-trained group; no differences in all other architectural measurements; or calf muscle strength, power, endurance or flexibility between groups were identified. However, one of the key findings emerging from this study is the variable resistance training practices in endurance runners; and that resistance training practices were not aligned to current evidence-based guidelines for resistance training. Resistance training has a critical role in enhancing endurance running performance, injury prevention and rehabilitation. Future research should investigate the knowledge, attitudes and practices of endurance runners regarding resistance training; to facilitate the development of appropriate education interventions, and to effectively disseminate evidence-based training guidelines to lay communities.